Locally soluble groups with the restrictions on the generalized norms - Lukashova, T. (Algebra and Discrete Mathematics, 2020)
The author studies groups with given restrictions on norms of decomposable and Abelian non-cyclic subgroups. The properties of non-periodic locally soluble groups, in which such norms are nonidentity and have the identity intersection, are described.